Survey of Free-living Amoeba from Soil Sources using Culture Method in Narathiwat Province, Thailand - Hounkong, Kruawan; Sukchan, Phnom; Sujiwattanarat, Penporn; Dangmanee, Nattakan; Sornying, Peerapon (Princess of Naradhiwas University Journal, 2021)
Acanthamoeba spp. are free-living amoeba found in the natural environment Acanthamoeba spp. can cause Acanthamoeba keratitis (AK) and Granulomatous Amoebic Encephalitis (GAE) in human. The aim of this study was to survey the prevalence of Acanthmoeba spp. from soil samples including Bacho, Yi-ngo and Ra-ngae district in Narathiwat province, Thailand by culture method. Identification of Acanthamoeba strains was based on the morphology of the cyst forms according to the criteria given by Pussard and Pons. Of the 60 soil samples, the result showed that the overall prevalence of Acanthamoeba spp. was 73.3%. No significant difference in prevalence was found on sampling areas in each district (p>0.05). Based on Pussard and Pons classification, the most Acanthamoeba cysts were classified as group III in all of the 3 districts. The highest cyst number was found in Yi-ngo district at 45 percent while Ra-ngae and Bacho district were 35 and 30 percent, respectively, followed by group II that was found in Ra-ngae district at 25 percent. In addition, group I was found in Bacho district at 15 percent. This is the first report of Acanthamoeba spp. from soil sources in Narathiwat province of Thailand, and the results suggest that more attention is needed to protect, which might be the population in the areas can infect Acanthamoeba spp.